Можливості впливу тендерних стереотипів на вибор професії молоддю - Слюсар, А. П. (ХНУРЕ, 2019)
The article is devoted to the analysis of the problem of gender stereotypes in the modern labor market, their influence on the choice of future professional activities by young people and on further self-realization.